Implementation of Moral Values ​​Underlying Awareness of Covering the Private Parts of Hijab-wearing Female Students at Universitas Islam Bandung - Muhammad, Giantomi; Azizah, Hasna Nur; Suhardini, Asep Dudi (Universitas Negeri Semarang, 2025)
Abstract ____________________________________________________________ The importance of covering the intimate parts is mandatory for a Muslim woman. Adequate knowledge is required to implement the requirement to cover the private parts properly. Knowledge regarding aspects of morality is an integral part for a Muslim woman so that it is embedded in the personality. Bandung Islamic University students are required to cover their intimate parts while on campus. These rules have been stipulated by the Chancellor's binding regulations. There is a need to strengthen the underlying aspects of morality so that female students remain consistent in covering their intimate parts. The aim of this research is to determine the aspects of morality that underlie the awareness of covering the intimate parts of female students who wear the hijab at Bandung Islamic University. This research uses a qualitative approach with phenomenological methods. Data collection techniques using documentation, interviews and observation. Data analysis techniques are carried out through data reduction, data interpretation, data verification and conclusions. The results of the research reveal the underlying aspects of morality in terms of moral knowledge, moral feelings and moral actions of female hijab-wearing students at Bandung Islamic University. These aspects are strengthened by the regulations implemented so that they can be implemented consistently.